A Massive White Dwarf or Low-mass Neutron Star Discovered by LAMOST - Xinlin Zhao; Song Wang; Pengfei Wang; Chuanjie Zheng; Haibo Yuan; Jifeng Liu (The Astrophysical Journal)
We report the discovery of a close binary J0606+2132 (Gaia DR3 3423365496448406272) with P _obs = 2.77 days containing a possible massive white dwarf (WD) or a neutron star (NS) using LAMOST spectroscopic data. By a joint fitting of the radial velocity from LAMOST and the light curve from TESS, we derived a circular Keplerian orbit with an inclination of i = 81.°31 ${}_{-7.85^° }^{+6.26^° }$ , which is consistent with that derived from $v\,\sin \,i$ . Together with the mass of the visible star, we derived the mass of the invisible object to be ${1.34}_{-0.40}^{+0.35}{M}_{\odot }$ . Spectral disentangling with the LAMOST medium-resolution spectra shows no absorption feature from an additional component, suggesting the presence of a compact object. No X-ray or radio pulsed signal is detected from ROSAT and FAST archive observations. J0606+2132 could evolve into either a Type Ia supernova or an NS through accretion-induced collapse if it is a WD or into an intermediate-mass X-ray binary if it is an NS.